Extract of Ephedra sinica Stapf Induces Browning of Mouse and Human White Adipocytes - Se-Jun Park; Dong-Hyun Shon; Yang-Hwan Ryu; Yong Ko (Foods, 2022)
Browning of adipocytes using herbal extracts is an attractive and realistic strategy for obesity treatment. Ephedra sinica Stapf (E. sinica) is an Asian traditional medicine known to activate brown adipocytes. To evaluate the effect of E. sinica (EEs) on the browning of white adipocytes, expression levels of browning markers, including uncoupling protein 1 (UCP1), were determined using qPCR, Western blot, and immunocytochemistry after mature mouse inguinal preadipocyte (mIPA) and human adipose-derived stem cells (hADSCs) were treated with EEs. In addition, mitochondrial activity was determined by analyzing MitoTracker staining, mtDNA copy number, and oxygen consumption rate (OCR). Treatment with EEs suppressed lipid accumulation and expression levels of adipogenic markers, including Pparg, during mIPA differentiation. In mature mIPA and hADSCs browning markers, including Ucp1, were up-regulated by EEs. In addition, EEs increased expression of mitochondrial genes, mtDNA copy number, and OCR. EEs showed a dual function: inhibiting adipogenesis in immature preadipocytes, and promoting thermogenesis via browning in mature white adipocytes. Therefore, E. sinica is a potential herb for regulating energy metabolism by inducing the browning process.